Rhizosphere Spatiotemporal Organization–A Key to Rhizosphere Functions - Vetterlein, Doris; Carminati, Andrea; Kögel-Knabner, Ingrid; Bienert, Gerd Patrick; Smalla, Kornelia; Oburger, Eva; Schnepf, Andrea; Banitz, Thomas; Tarkka, Mika Tapio; Schlüter, Steffen (Frontiers in Agronomy, 2020)
Resilience of soils, i.e., their ability to maintain functions or recover after disturbance, is closely linked to the root-soil interface, the soil's power house. However, the limited observability of key processes at the root-soil interface has so far limited our understanding of how such resilience emerges. Here, we hypothesize that resilience emerges from self-organized spatiotemporal patterns which are the result of complex and dynamic feedbacks between physical, chemical, and biological processes occurring in the rhizosphere. We propose that the combination of modern experimental and modeling techniques, with a focus on imaging approaches, allows for understanding the complex feedbacks between plant resource acquisition, microbiome-related plant health, soil carbon sequestration, and soil structure development. A prerequisite for the identification of patterns, underlying processes, and feedback loops is that joint experimental platforms are defined and investigated in their true 2D and 3D geometry along time. This applies across different scientific disciplines from soil physics/chemistry/microbiology to plant genomics/physiology and across different scales from the nano/microscopic scale of the root soil interface, over the radial profiles around single roots, up to the root architecture and plant scale. Thus, we can move beyond isolated reductionist approaches which have dominated in rhizosphere research so far.